Skills in basic operation using pemdas rule of grade 8 students - Jerson M. Quijano and Vince Roniel U. Panganiban. 4 0 16; 5 (2016)
ABSTRACT: The purpose of the study is to improve the students kills in solving Mathematical expressions using the PEMDAS rule and without the use of calculators. The researchers applied teaching strategies to improve the students level of skills. The gathering of the data is in the form of interview, pre-test, exercises and post-test. These tests scores are used in order to measure the level of skills of the students. The results of both tests are analyzed and then compare to each other to know the significance of the study. The results suggest that students tend to learn more in basic skills when using different teaching strategies. The level of skills of the students improved after the use of teaching strategy - the use of manipulatives.
Thesis: (Bachelor of Secondary Education with Specialization in Mathematics) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2